Digital Culture and Its Impact on New Testament Interpretations and Religious Practices - Tari, Ezra; Revilla, Abdiel Enrique Sánchez (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Many aspects of life, including religious ideas and rituals, have been profoundly shaped by technology. It has affected how members of different faith communities interact and commune with God. These days, digital channels act as forums for conversations that could influence religious perspective. Here, the term "digital culture" describes technologically driven social interactions including social media, websites, and easy information access. This study is a quantitative study aimed at investigating the relationship between religious customs and the cultural changes brought about by digitization. Data was collected from 36 respondents by using a questionnaire. The results draw attention to the complicated relationship in modern culture between faith and technology. In Christian communities today, effective communication calls not just for sharing knowledge but also interacting with digital resources. Christians' practice of their faith has evolved with the availability of online worship events and prayer meetings. The findings also underline the need of mutual support—both psychological and financial—through trying circumstances. Christians have additional means to study scriptures and participate in worship because to increasing digital resources.